2012 Bower Award for Business Leadership presented to John T. Chambers, Cisco Systems, Inc. | San Jose, California. Issue 7 (July 2015) - Sullivan, Brian
Abstract John T. Chambers receives the 2012 Bower Award for Business Leadership for shaping Cisco Systems, Inc. into one of the world's most widely respected and successful technology companies, providing business and consumer technologies that allow millions of people to connect to each other through computer networking and the Internet, and for his leadership by example in corporate responsibility and personal philanthropy.